A-DROP system for prognostication of NHCAP inpatients. Issue 8 (August 2017) - Koizumi, Takeshi; Tsukada, Hiroki; Ito, Kazuhiko; Shibata, Satoshi; Hokari, Satoshi; Tetsuka, Takafumi; Aoki, Nobumasa; Moro, Hiroshi; Tanabe, Yoshinari; Kikuchi, Toshiaki
Abstract: Nursing and healthcare-associated pneumonia (NHCAP) is a category of healthcare-associated pneumonia that was modified for the healthcare system of Japan. The NHCAP guidelines stated the difficulty in assessing the severity classifications, for instance, A-DROP. We compared the usefulness of different severity classifications (A-DROP, CURB-65, PSI, and I-ROAD) in predicting the prognosis of nursing and healthcare-associated pneumonia. We conducted a retrospective analysis on 303 adult patients hospitalized for nursing healthcare-associated pneumonia and community-acquired pneumonia, which were diagnosed at the Department of Respiratory Medicine of Niigata General City Hospital between January 2012 and December 2014. We evaluated 159 patients with community-acquired pneumonia and 144 with nursing and healthcare-associated pneumonia. In the nursing and healthcare-associated pneumonia group, 30-days mortality and in-hospital mortality rates were 6.5% and 8.7%, respectively, in severe cases and 16.1% and 25.0%, respectively, in the most severe cases, based on A-DROP. With I-ROAD, these rates were 11.1% and 11.1%, respectively, in group B and 14.9% and 20.7%, respectively, in group C. With PSI, the rates were 2.3% and 6.8%, respectively, in class IV and 14.3% and 19.8%, respectively, in class V. Despite some variability due to the small sample size, both the 30-days and in-hospital mortality rates increased as the severity increased. In this study, both the 30-days mortality and in-hospital mortality rates in the nursing and healthcare-associated pneumonia group tended to increase in severity with the A-DROP. We found that A-DROP was useful in predicting the prognosis of nursing and healthcare-associated pneumonia.